A cidade sob o olhar da periferia : aspectos do cotidiano dos moradores do Morro dos Alagoanos - Barros, Ana Maria Leite de (2010)
This work looks forward to understand some aspects of Morro dos Alagoanos, community which belongs to Caratoíra neighborhood (Vitória/ES), especially regarding its insertion in the city as a living space. Initially is discussed the importance of the scale achieved by the urbanization in the contemporary world, as a way to understand, how Morro dos Alagoanos was born and its occupation consolidates, inserted in the urban expansion process of Vitória city. However, the priority is the discussion related to the informal urbanization, first contextualizing this process in Brazil and after in the Vitória city, because the starting of the occupation which formed Morro dos Alagoanos is inserted in the process that resulted in the creation of the Vitória suburb from residential spaces constituted informally. In a second step, the work proceeds clarifying the choice of a neighborhood as a spatial cutoff for the research development, since it is not only one of the subdivisions which compose the city, but it is the place in which the relations between inhabitants, living place and the city, are established in a more direct way. For this purpose are also discussed some key concepts to comprehend everyday relations of the neighborhood inhabitants with its living place. Third part of the work takes care fundamentally of the Morro dos Alagoanos community, seeking to build the historical path of its formation, the current status of the community, especially regarding to the relations that the residents establishes everyday among themselves and with the place, which is more evident in a complex community, experienced and considered from many different forms, in the joy and in the fatigue of everyday life of its residents as well as in its reflection on their place in the city.